Understanding Workplace Spirituality Through a Bibliometric Analysis - Setiawan, Audita; Limakrisna, Nandan; Warsindah, lucy; Indriyati, Citra (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Purpose – The goal of the current study is to investigate the bibliometric analysis of research articles on workplace spirituality that have been included in the Web of Science index. Methodology/approach – The VOS viewer software tool and Biblioshiny, which is used to produce maps, were used in conjunction with Excel sheets to analyze the data in terms of frequency and percentage. A total of 367 research papers that were published between 2020 and 2022 were chosen for this study. Findings – The analysis of the findings revealed instrumental knowledge, including top contributing countries in publication, affiliation, top contributing authors, also author keyword co-occurrence and authors keyword overlay. It is observed from the analysis that a high volume of the research was initiated from India followed by China and Indonesia. The trend show growth in year 2021. Novelty/value – These results hope will provide future researchers more options to take into account as a starting point before beginning a study on workplace spirituality. Keywords Workplace Spirituality, Bibliometric,Web of Science